2020
DOI: 10.29252/jmis.5.2.59
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Selected Data-mining techniques in ICU Mortality Risk Prediction in Imam Hossein hospital

Abstract: Aim: Intensive Care Unit (ICU) is a ward that is critical to improving the health status of critical conditions. Data mining seems to be a good way to optimize the use of resources. Identifying and analyzing the risk factors associated with mortality will lead to more efficient and accurate planning of hospitalization and interventions. In this study, the prediction of mortality of patients in the intensive care unit of Imam Hossein Hospital in Tehran with data mining techniques is discussed. Methods: Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The results of sensitivity analysis of the MLP NN sel model showed that GCS, age, HCO3, BUN, Cr, Hr and Hct are the most important determinants of mortality in ICU patients, respectively. In line with the results of the present study, Asgari reported that glucose, relative thromboplastin time, white blood cells, systolic blood pressure, creatinine, albumin, and bilirubin are the most effective variables in predicting mortality in the ICU [ 39 ]. Barfod et al introduced some vital signs, including peripheral oxygen saturation, RR, SBP, and GCS, as the predicting factors of mortality in the ICU.…”
Section: Discussionsupporting
confidence: 88%
“…The results of sensitivity analysis of the MLP NN sel model showed that GCS, age, HCO3, BUN, Cr, Hr and Hct are the most important determinants of mortality in ICU patients, respectively. In line with the results of the present study, Asgari reported that glucose, relative thromboplastin time, white blood cells, systolic blood pressure, creatinine, albumin, and bilirubin are the most effective variables in predicting mortality in the ICU [ 39 ]. Barfod et al introduced some vital signs, including peripheral oxygen saturation, RR, SBP, and GCS, as the predicting factors of mortality in the ICU.…”
Section: Discussionsupporting
confidence: 88%